Measuring SO2, CO2, and Radon Gases Concentration in the Areas Surrounding the Dora Refinery (Journal of Engineering, 2025)
This research aims to evaluate the levels of some air pollutant gases, namely sulfur dioxide (SO2), carbon dioxide (CO2), and radon (Rn222) in the residential areas surrounding the Dora refinery, south of Baghdad. Several locations were selected from residential areas representing different directions relative to the refinery, taking into account the distance from the emission source and the environmental characteristics of the site. In this study, gas detection techniques were applied, using a multi-gas detector in the areas surrounding the Dora refinery. Concentrations were collected over three consecutive months, with 89 readings taken at 14 locations in the areas surrounding the Dora refinery. The results showed that the average value of sulfur dioxide (SO2) was 0.8 ppm, equivalent to 2.288 mg/m3, with the highest reading at 2.8 ppm, equivalent to 8.008 mg/m3 recorded at the Jadriya intersection. While the lowest reading was recorded at Al-Zafaraniya intersection, which reached 0.3 ppm, which is equivalent to (0.8580 mg/m3), which is less than the limit recommended by the World Health Organization. As for carbon dioxide gas (CO2), the highest reading was recorded in the Jadriya area, site 4, which reached 888.6 ppm. The lowest reading was recorded in the Dur Al-Masafie area, site 3, which reached 234.7 ppm. As for radon gas (Rn222), the highest reading was recorded at 317.834 Bq/m3 in the Al-Saydiya area, site 1, and the lowest reading was recorded in the Al-Taama/Al-Dawra area, where it reached 13.542 Bq/m2. No value higher than the internationally recommended values was recorded. This study highlights the importance of periodic monitoring of the concentrations of polluting gases in the air, especially in areas adjacent to oil facilities, due to their direct environmental and health impacts on the population.